TRICKLE IRRIGATION SAND CUM HYDROCYCLONE FILTER PERFORMANCE AS AFFECTED BY IMPURITY, SIZE AND CONCENTRATION - Pimpale, A.R.; Hiwase, S.S.; Bhende, S.M.; Bhuyar, R.C. (Journal of Soil and Water Conservation, 2022)
Impurity, particle size and concentration were tested for their effect on the sand cum hydrocyclone filter performance. Three impurity sizes were used at four different concentrations. Smaller size impurity particles found to reach predetermined pressure drop limit (7.9 m of water) early as compared to larger ones. Increasing influent impurity concentration caused greater weight of sand to accumulate and allowed comparatively less amount of water to pass, through the filter before reaching the maximum pressure drop limit.